Extended DNA analyses: Surveillance technology at the intersection of racism and sexism - Isabelle Bartram; Tino Plümecke; Andrea zur Nieden (Internet Policy Review, 2021)
Genetic data contains a multitude of highly personal information and is therefore deemed an especially sensitive data category by data protection laws. But technological advances and the increasing demands of security policymakers have led to the continuous expansion of governmental authority over DNA extraction, analysis and storage. The protection of women from sexual crimes is often put forward as grounds to legitimise these expansions. Sexism and racism intersect in the most recent debate on further policy change, building on existing public fears of the threat posed by unknown male migrants to white German women and presenting controversial DNA technology as a solution.
Keywords: 300; Surveillance; Genetic data; DNA